Idiopathic Sporadic Onychomadesis of Toenails. (29th June 2016) - Suchonwanit, Poonkiat; Nitayavardhana, Sunatra
Abstract : Onychomadesis is a clinical sign of nail plate separation due to transient or permanent arrest of nail matrix activities. Onychomadesis can be considered as a severe form of Beau's line. This condition usually occurs after trauma, causal diseases, or medications, yet it rarely occurs as an idiopathic condition. We report a case of a 38-year-old Thai female who developed recurrence onychomadesis in several toenails in the absence of predisposing factors or associated conditions. To the best of our knowledge, our patient is the first reported case of idiopathic onychomadesis limited to toenails.